Rubella virus-specific humoral immune responses and their interrelationships before and after a third dose of measles-mumps-rubella vaccine in women of childbearing age - Haralambieva, Iana H. (Vaccine, 2019)
In the U.S., measles, mumps, and rubella vaccination is recommended as two vaccine doses. A third dose of measles-mumps-rubella (MMR) vaccine is being administered in certain situations (e.g., identified seronegativity and during outbreaks). We studied rubella-specific humoral immunity (neutralizing antibody, enzyme-linked immunosorbent assay/ELISA IgG titer and antibody avidity) and the frequencies of antigen-specific memory B cells before and after a third dose of MMR-II in 109 female participants of childbearing age (median age, 34.5 years old) from Olmsted County, MN, with two documented prior MMR vaccine doses. The participants were selected from a cohort of 1,117 individuals if they represented the high and the low ends of the rubella-specific antibody response spectrum. Of the 109 participants, we identified four individuals (3.67 % of all study participants; 7.14 % of the low-responder group) that were seronegative at Baseline (rubella-specific ELISA IgG titers < 10 IU/mL), suggesting a lack of protection against rubella before receipt of a third MMR vaccine dose. The peak geometric mean neutralizing antibody titer one month following the third dose of MMR vaccine for the cohort was 243 NT(50) (CI; 241, 245), which is expected for a cohort with two doses of MMR, and the peak geometric mean IgG titer was 150 IU/mL (CI; 148, 152) with no seronegative individuals at Day 28. One-third of all subjects (31.8% for the neutralizing antibody; 30.8% for the IgG titer) experienced a significant boost (≥ 4-fold) of antibody titers one month following vaccination. Antibody titers and other tested immune-response variables were significantly higher in the high-responder group compared to the low-responder group. The frequencies of rubella-specific memory B cells were modestly associated with the antibody titers. Our study suggests the importance of yet unknown inherent biologic and immune factors for the generation and maintenance of rubella-vaccine-induced humoral immune responses.